2008
DOI: 10.1515/cclm.2008.192
|View full text |Cite
|
Sign up to set email alerts
|

Prohormone brain natriuretic peptide (proBNP), BNP and N-terminal-proBNP circulating levels in chronic hemodialysis patients. Correlation with ventricular function, fluid removal and effect of hemodiafiltration

Abstract: Despite their elimination, BNP, NT-proBNP and proBNP could be potential markers of left ventricular remodeling in chronic renal failure patients on hemodialysis. According to these results, their cut-off values, however, need to be re-evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
4
42
1
2
Order By: Relevance
“…These findings contrast with those of a longitudinal cohort study demonstrating that baseline hypertension at dialysis inception and residual hypertension at 1-year post-dialysis commencement were associated with a significantly increased risk of mortality without any survival disadvantage associated with low blood pressure (45), and those of a prospective cohort study of 692 haemodialysis patients which reported that a mean arterial blood pressure > 110 mmHg was associated with an increased risk of all-cause and cardiovascular death after adjusting for demographic factors and co-morbid conditions (46). Finally, a recent meta-analysis of 8 randomised controlled trials of antihypertensive therapy in dialysis found significant reductions in the risks of fatal and nonfatal cardiovascular events and all-cause mortality in actively treated patients compared with controls supporting the hypothesis that hypertension portends an adverse prognosis in the dialysis population(47).…”
Section: Hypertensioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings contrast with those of a longitudinal cohort study demonstrating that baseline hypertension at dialysis inception and residual hypertension at 1-year post-dialysis commencement were associated with a significantly increased risk of mortality without any survival disadvantage associated with low blood pressure (45), and those of a prospective cohort study of 692 haemodialysis patients which reported that a mean arterial blood pressure > 110 mmHg was associated with an increased risk of all-cause and cardiovascular death after adjusting for demographic factors and co-morbid conditions (46). Finally, a recent meta-analysis of 8 randomised controlled trials of antihypertensive therapy in dialysis found significant reductions in the risks of fatal and nonfatal cardiovascular events and all-cause mortality in actively treated patients compared with controls supporting the hypothesis that hypertension portends an adverse prognosis in the dialysis population(47).…”
Section: Hypertensioncontrasting
confidence: 99%
“…BNP and NT-proBNP have a number of proven clinical applications in the general population, including improving the accuracy of clinical assessment for diagnosing cardiac failure in patients presenting with dyspnoea (44,45) and estimating prognosis in patients with an established diagnosis of cardiac failure (46). Over the last decade, 9 randomised controlled trials have examined the role of BNP / NT-proBNP monitoring in guiding heart failure therapy compared to specialist care alone.…”
Section: Biochemistry and Established Clinical Applications Of The B-mentioning
confidence: 99%
See 1 more Smart Citation
“…The BNP and NT-proBNP have been investigated in other volume-overloaded states. A study of 31 dialysis patients without evidence of cardiac failure found that BNP and NT-proBNP values decreased with hemodialysis [13]. This drop did not correlate with the post hemodialysis fluid removal or weight decrease [13].…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…A study of 31 dialysis patients without evidence of cardiac failure found that BNP and NT-proBNP values decreased with hemodialysis [13]. This drop did not correlate with the post hemodialysis fluid removal or weight decrease [13]. In another small study, Giglioli et al, assessed 15 patients with congestive heart failure undergoing slow continuous ultrafiltration.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%